240. Estimated Clinical and Economic Impact Through Use of an Initial Specimen Diversion Device to Reduce Blood Culture Contamination: A Cost–benefit Analysis. (26th November 2018) - Skoglund, Erik; Dempsey, Casey; Garey, Kevin W
Abstract: Background: Blood culture contamination results in increased hospital costs and unnecessary patient-exposure to antimicrobials. We sought to evaluate the potential clinical and economic benefits of a novel blood culture diversion device when routinely utilized for blood culture collection in the emergency department (ED) of a quaternary care medical center. Methods: A decision analysis model was created. Probabilistic costs were determined from published literature and direct observation of pharmacy/microbiology staff. The primary outcome was the expected per-patient cost savings (microbiology, pharmacy, and indirect hospital costs) after initial specimen diversion device (e.g., SteriPath) implementation in the ED using a hospital perspective. Indirect hospital costs included increased hospital length of stay, additional procedures, adverse drug reactions, and hospital-acquired infections. Models were created for hospitals that routinely or do not routinely use rapid diagnostic tests (RDT) on positive blood cultures. Results: The routine implementation of an initial specimen diversion device for blood culture collection in the ED was cost-beneficial compared with conventional blood culture collection methods and was also associated with a reduction in antibiotic usage, adverse drug reactions and hospital-acquired infections. When implemented in a hospital utilizing RDT with a baseline contamination rate of 6%, initial specimen diversion device use was associated with a cost savings of $272 (3%) per blood culture in terms of overall hospital costs and $28 (5.4%) in direct-only costs. Main drivers of cost included the baseline rate of contamination in the ED and the duration of antibiotics given to patients with negative blood cultures. Conclusion: Implementation of an initial specimen diversion device is estimated to be a cost-beneficial strategy to reduce the clinical and economic impact of blood culture contamination in terms of microbiology, pharmacy, and wider indirect hospital costs. Disclosures: K. W. Garey, Merck & Co.: Grant Investigator, Grant recipient.